3D contact patch measurement inside rolling tyres. (February 2017) - Guthrie, A. Glenn; Botha, Theunis R.; Els, P. Schalk
Highlights: Dynamic contact patch measurement inside rolling tyres. Mechanical stabilising system for constant observation of contact area. Full 3D field stereo computer vision deformation measurement. Large deformed contact area is made available as a 3D point cloud. Has the potential to provide insight into never before measured tyre dynamics. Abstract: This paper presents a novel method for capturing the 3D profile of the inside of a rolling off-road vehicle tyre at the tyre-road contact region. This method captures the contact region at all times as the vehicle negotiates obstacles. The system uses a pair of inexpensive digital cameras (capable of capturing up to 300 frames per second) and features a purely mechanical stabilisation system to ensure that the cameras capture the contact region at any wheel speed or vehicle acceleration. The captured images are processed using 3D computer vision techniques using an open source computer vision library called OpenCV. Stereo image pairs are used to create clouds of 3D points showing the profile of the inside surface with good accuracy. Various obstacles were traversed with the deformed tyre profile being compared to the undeformed profile. The system improves on current measurement techniques used to measure the contact patch by capturing a large region of the contact patch, providing full 3D surface geometry, as well as remaining centred on the contact patch irrespective of wheel rotation. The system also enables other imaging techniques to be used such as digital image correlation to determine velocity profiles as well as strain measurements.